Prototyping of nanophotonic grating back contacts for light trapping in planar silicon solar cells. Issue 7 (31st March 2016) - Smeets, Michael; Lentz, Florian; Richter, Alexei; Augarten, Yael; Bittkau, Karsten; Ding, Kaining; Carius, Reinhard; Rau, Uwe; Paetzold, Ulrich W.
Abstract : Nanophotonic gratings can be used for efficient light trapping in crystalline silicon solar cells. A common challenge is the high quality surface passivation, when applying such gratings. In this article, we report on the prototyping of the application of nanophotonic grating back contacts to planar silicon heterojunction solar cells for improved light trapping. These back contacts are processed after the Si wafer passivation, omitting any direct texturing of the absorber layer. Thereby, maintaining the integrity of the planar passivation layer of high quality and simultaneous light trapping is realized. The induced light‐trapping effect is further studied by photoluminescence imaging, external quantum efficiency measurements as well as absorptance measurements of solar cells applying nanophotonic grating back contacts of different grating periods. A clear correlation is found for the three characterization methods which allows the optimal period for efficient light trapping in the investigated solar cells to be identified. For the optimized grating period of the nanophotonic grating back contact an increased short‐circuit current density is obtained and the power conversion efficiency is enhanced by 0.4%, absolute.